Classification of voting algorithms for N-version software - Tsarev, R. Yu; Durmus, M. S.; Ustoglu, I.; Morozov, V. A. (IOP PUBLISHING LTD, 2018)
A voting algorithm in N-version software is a crucial component that evaluates the execution of each of the N versions and determines the correct result. Obviously, the result of the voting algorithm determines the outcome of the N-version software in general. Thus, the choice of the voting algorithm is a vital issue. A lot of voting algorithms were already developed and they may be selected for implementation based on the specifics of the analysis of input data. However, the voting algorithms applied in N-version software are not classified. This article presents an overview of classic and recent voting algorithms used in N-version software and the authors' classification of the voting algorithms. Moreover, the steps of the voting algorithms are presented and the distinctive features of the voting algorithms in N-version software are defined.
Keywords: RELIABILITY; Engineering; Physics